Controversy over GM maize in Peru - Rimachi Gamarra, Luis Fernando; Alcántara Delgado, Jorge Enrique; Ortiz Rios, Rodomiro Octavio (Springer Nature, 2020)
The INIA analysed the source and quantity of maize imports, records of seed cultivars, their genetic diversity and planting location. Evidence of transgenes was discovered in only some of the poultry grain samples. This finding is not surprising. We believe that the Barranca region today is unlikely to be a primary centre of maize diversity. However, farmers there may be growing maize hybrids and other cultivars that have seeds of foreign origin.